Role of common carp (Cyprinus carpio) in aquaculture production systems - Rahman, Mohammad Mustafizur (Taylor & Francis, 2015)
Common carp (Cyprinus carpio) is considered to be a very important aquaculture species in many Asian and some European countries. It affects the aerobic decomposition of organic matter and nutrient availability in the water column via bioturbation of benthic sediment during feeding on benthic organisms. If the density of common carp is not excessive, an increase in nutrient availability may enhance photosynthesis and plankton production, whereas if it is excessive, it causes dramatic ecological disruption at both the community and ecosystem levels by changing the abiotic properties of the water. Therefore, the density of common carp is a very important factor that has a great effect on the aquatic ecosystem. The critical density of common carp largely depends on its habitat. In polyculture ponds, water quality, natural food resources and fish growth are strongly affected when the density of common carp approaches more than about 1000 kg ha−1. The critical density can be doubled if artificial feed is supplied to the carp. When its preferred food is not sufficient, the common carp switches to less preferred food and changes its behaviour and feeding niche. These factors make common carp a potential candidate not only for monoculture but also for polyculture ponds. This article reviews the role of common carp on the aquatic ecosystem, and the production and behaviour of fish in aquaculture production systems.